Hubungan Derajat Kegiatan Fisik Serta Konsumsi Air Terhadap Kejadian Konstipasi Mahasiswa Fakultas Kedokteran Universitas Islam Bandung - Maulina Isnaini Sugiantoro; Mirasari Putri; Samsudin Surialaga (UNISBA Press, 2023)
Abstract. This literature study was conducted to collect data on whether there is an incidence of constipation in students of the Faculty of Medicine at the Islamic University of Bandung due to several factors causing constipation, namely low levels of physical activity and low water consumption. where Constipation is reduced bowel movements associated with hard stools and difficulty having bowel movements (BAB). Several factors that can increase constipation are physical activity and lack of water consumption. A low level of physical activity will reduce intestinal peristalsis, while less water consumption will decrease the stretch response of the stomach and increase fecal water uptake in a person's low hydration situation. This literature study uses an observational analytic research design with a cross sectional study method on willing respondents, namely students of the Faculty of Medicine, Bandung Islamic University in 2021. Physical activity levels were measured using the International Physical Activity Questionnaires (IPAQ) questionnaire, water consumption levels were measured using daily adequacy rates RI Ministry of Health fluids and constipation variables were measured using the Patient Assessment of Constipation-Symptomp (PAC-SYM) questionnaire. The conclusion of this study is that there is no significant relationship between the level of physical activity and water consumption on the incidence of constipation in students of the Faculty of Medicine, Islamic University of Bandung Keywords: Consipation, Water consumption, Level of physical activity Abstrak. Studi litelatur ini dilakukan untuk mengumpulkan data apakah terdapat kejadian konstipasi pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung yang disebabkan karna beberapa faktor penyebab dari konstipasi yaitu derajat aktivitas fisik yang rendah dan konsumsi air putih yang rendah. dimana Konstipasi adalah berkurangnya pergerakan usus yang berasosiasi dengan keadaan feses yang keras dan sulit untuk melakukan Buang Air Besar (BAB). Beberapa faktor yang dapat meningkatkan konstipasi adalah aktifitas fisik dan konsumsi air putih yang kurang. Tingkat aktifitas fisik yang kurang akan menurunkan gerak peristaltik usus sedangkan konsumsi air yang kurang akan menurunkan respon regang lambung dan meningkatkan ambilan air feses dalam situasi hidrasi seseorang yang rendah. Studi litelatur ini menggunakan desain penelitian analitik observasional dengan metode cross sectional study pada responden yang bersedia yaitu mahasiswa Fakultas Kedokteran Universitas Islam Bandung tahun 2021. tingkat aktivitas fisik diukur menggunakan kuesioner International Physical Activity Questionnaires (IPAQ), tingkat konsumsi air putih diukur menggunakan angka kecukupan harian cairan Kemenkes RI dan variabel konstipasi diukur menggunakan kuesioner Patient Assesment of Constipation-Symptomp (PAC-SYM). Simpulan penelitian ini adalah tidak terdapat hubungan yang signifikan antara tingkat aktifitas fisik dan konsumsi air terhadap kejadian konstipasi pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung Kata Kunci: Konstipasi, Konsumsi air, Tingkat aktifitas fisik